Produce an emulsion paint by using vegetable oils painted on plastic brick - Nurfatin Husna, Najamulharis; Nuranis Yasira, Abd Halim; Mohammad Aidil Shafiq, Mustafa; Fatin Zafirah, Mansur (2022)
Emulsion paint is water-based and contains coloured polymer particles. These pigment-containing particles may contain acrylic or vinyl to make them more durable and easier to apply to walls and ceilings. When paint dries, the particles mix to form a wall film. Emulsion paint is used indoors and outdoors. Interior emulsion paint is required when painting a room. Emulsion paint can be used for a complete redecoration, a feature wall, or a touch-up before moving. Some emulsion paints trap heat, increasing the room's temperature. Cracking, fading, blistering, and poor aesthetics are common emulsion paint issues. Heat-reflecting paints are used on building exteriors to reduce solar heat. Compared to oil-based paints, emulsion paints are less harmful, with fewer volatile organic compounds. Emulsion paints have a mild-to-high washability indicator. Washability affects surface lustre. Depending on the type, some emulsion paints can be washed. Emulsion paint is glossy, semi- glossy, eggshell, matt, and smooth. The paint is water-resistant, making it easy to clean. There are many ways to apply paint. Spraying, dipping, flowing, rolling, and brushing are options. Emulsion paint is nonflammable and odourless. It's great for kitchens and bathrooms. Paintings can fail for many reasons. Misapplication, defective paint, incorrect paint selection, or environmental exposure are common causes. There are more fundamental reasons why paintings fail than these four. Emulsion paint has a better finish than distemper and doesn't dry or crack in sunlight.Their colour doesn't fade or peel when wet. Less toxic, easy to apply, and safe for wood, concrete, and metal. Emulsion paint doesn't dry or crack in sunlight and has a better finish than distemper. They don't peel or fade when wet. This research aims to develop an emulsion paint using vegetable oil that can help with temperature changes.